(untitled) (Stamford Journal of Microbiology, 2017)
Plant nutrients are vital component of sustainable agriculture as they are essential for the production of crops and healthy food. Chemical fertilizer or pesticides may have huge influence to increase the heavy metal and resistant microbes in soil as well as in crops. In order to provide an experimental evidence on the positive impact of bio-fertilizer instead of chemical fertilizer on agricultural field, present study attempted to collect 50 samples of Brassica oleracea (25 were treated with bio-fertilizer and 25 were chemically treated) from different agricultural land of rural area in Bangladesh. The samples were processed to examine the microbiological and clinical aspects of both bio-fertilizer and chemical fertilizer on vegetables through several common, traditional and replicable cultural and biochemical tests. Both samples were found to be contaminated with total viable bacteria and fungi up to the range 108 & 106cfu/g, respectively. The elevated range of pathogenic contamination (Staphylococcus spp., Bacillus spp., Pseudomonas spp.) was found in both samples within the range of 102 to 106cfu/g. In case of biofertilizer treated vegetable the contamination of Staphylococcus spp. was prominent up to 106 cfu/g and the same existence was found for chemically treated vegetable. Bacillus spp. and Pseudomonas spp. were found 104 & 105 cfu/g, respectively in biofertilizer treated vegetable while the contamination was noticed up to 102 & 104 cfu/g in chemically treated vegetable respectively. Another important era of this study is drug resistant pattern, most of the isolates exhibited resistance against commonly used antibiotics while several isolates were noted to be multi-drug resistant (MDR). The drug resistance strains were remarkably high in chemically treated vegetable whereas maximum antibiotics were extremely effective against the bacteria isolated from biofertlizer treated vegetable Stamford Journal of Microbiology, Vol.7(1) 2017: 23-27